(untitled) (Journal of Parents and Teachers, 1995)
The objective is for the baby to learn to differentiate between loud and soft sounds. The goal is for the baby to vocalize the letter “u” through auditory and visual stimulation. In addition, their ability to perform actions in response to music and hand movements will be observed.